(untitled) (Scientific Journal of Research Studies in Future Psychology, 2025)
The purpose of this study was to compare sexual performance and marital satisfaction in men with higher education and with no higher education. The purpose based research is theoretical- applied research. Depending on the nature and method of work, the research is correlation. The statistical population of this study was all married men with higher education and higher education in west Tehran in 1977. Due to the unavailability of official statistics on married men with higher education in west Tehran, 140 men and women with bachelors, master’s and doctor’s degrees were selected. Also 140 people with undergraduate and diploma education were also selected as peer group. Research tools were enrich marital satisfaction questionnaire and sexual function test. Multivariate analysis of variance was used to analyze the data. According to the result of covariance analysis, it was found that sexual function and its dimensions include desire, psychological stimulation, moisture, orgasm, satisfaction, sexual pain in men with higher education than men with higher education and marital satisfaction and dimensions including ideal distortion, satisfaction, communication, conflict resolution are higher in men with higher education than men with higher education.